Comparative study of structural behavior of CFRP tubes and traditional steel for pile and column applications compliance with international codes - Mahmoud El Gendy; Ibrahim El Arabi; Ahmed ELbarbary; Mohamed Hamed (Discover Civil Engineering)
Abstract Carbon Fiber-Reinforced Polymers (CFRPs) are highly valued in structural engineering due to their exceptional strength-to-weight ratio, durability, and corrosion resistance. While the design of reinforced concrete is governed by specific building codes, CFRPs have unique design considerations. This study delves into a comparative analysis of eight prominent building codes: ACI318 (American Concrete Institute), EC2 (Eurocode 2), ECP (Egyptian Code of Practice), BS8110 (British Standard), IS456 (Indian Standard), CP65 (Singapore Standard), CSA A23.3 (Canadian Standard), and HK CP (Hong Kong Code of Practice). The focus is on circular CFRP sections under bending and axial loads, which are more complex than rectangular sections. By comparing design requirements for general properties, bending, and column provisions, this paper aims to identify significant differences in design procedures. A software tool was developed to support analysis, and its results align closely with previous studies, available well-known programs, and interaction diagrams from various codes. Key factors influencing the capacity of CFRP structural elements, such as tube thickness and concrete strength, were investigated. The validated developed software is unique in analyzing columns and laterally loaded piles using the aforementioned building codes. The interaction diagrams generated by the program based on EC2, ECP, BS8110, and HK CP showed a high degree of similarity to those available in the design aids and charts, with the Mean Absolute Percentage Error (MAPE) values of less than 5%, indicating the software's accuracy in determining the ultimate load-carrying capacity of circular sections.